Desain Dashboard Command Center Kabupaten Bandung Barat Menggunakan Metode Design Thinking - Khoirullah, Debri; Nurul Sabrina, Puspita; Ashaury, Herdi (LPPM Universitas Mulia, 2025)
The advancement of digitalization requires local governments to provide information services that are efficient, well-structured, and user-friendly. This study aims to design the dashboard interface for the West Bandung Regency Command Center using the Design Thinking method. The approach involves five stages—empathize, define, ideate, prototype, and test—to deeply understand user needs and deliver appropriate design solutions. Data collection was conducted through interviews and observations, followed by the creation of an interactive prototype using Figma. Usability evaluation was carried out using the System Usability Scale (SUS). The results show that the redesigned dashboard presents government data in a more informative, structured, and intuitive manner and achieved a high SUS score during testing, with an average score of 75.625, categorized as Good. This study contributes uniquely to the development of user-centered government information systems, particularly in the context of command center applications. A limitation of this study is the small number of respondents in the usability test, due to the fact that the primary users of the system are executive officials who typically do not interact directly with the UI/UX. Thus, representatives from Diskominfo—who understand the interface from a technical and operational perspective—were selected as respondents. Given the limited number of personnel operating the command center, the involvement of four respondents was considered sufficient and contextually appropriate.